Strategies of Education and Cultural Attaché in Enhancing Educational Quality at Indonesian School Riyadh, Saudi Arabia - Cherry Rinaldi; Amrozi Khamidi; Kaniati Amalia; Mochamad Nursalim; Enny Roesminingsi; Muhamad Sholeh (Journal of Innovation and Research in Primary Education, 2026)
The role of Education and Cultural Attachés (Atdikbud) in managing Indonesian Schools Abroad (SILN) has become increasingly critical in maintaining educational quality for Indonesian citizens overseas. This study examines the strategic approaches employed by Atdikbud at the Indonesian Embassy in Riyadh to enhance educational quality at Sekolah Indonesia Riyadh (SIR). This research aims to analyze the strategies implemented by Atdikbud in improving educational quality, identify challenges encountered, and explore solutions applied in managing SILN within a multicultural context. Employing a qualitative case study approach, data were collected through in-depth interviews with Atdikbud, school principals, teachers, and parent representatives at SIR, complemented by direct observations and document analysis. Data analysis utilized the Miles and Huberman interactive model, incorporating data condensation, data display, conclusion drawing, and verification through triangulation. Findings reveal that Atdikbud implements five primary strategies: (1) policy harmonization between Indonesian and Saudi educational systems, (2) continuous professional development for educators, (3) infrastructure optimization through diplomatic channels, (4) cultural diplomacy integration in curriculum, and (5) stakeholder collaboration enhancement. Major challenges include resource limitations, cultural adaptation barriers, and bureaucratic complexities. Innovative solutions involve technology utilization, local community partnerships, and flexible policy implementation. In conclusion, atdikbud plays a pivotal strategic role in supporting Indonesian education abroad through adaptive leadership, cultural sensitivity, and diplomatic coordination. The study recommends strengthening inter-ministerial coordination, increasing resource allocation for SILN, and developing context-specific guidelines for educational diplomacy in multicultural settings.